Colonialism or supersanctions: sovereignty and debt in West Africa, 1871–1914. (27th February 2017) - Gardner, Leigh
Abstract: West Africa has been neglected in literature on sovereign debt before 1914. However, it presented arguably the biggest test of investors' willingness to overlook poor economic fundamentals due to colonial status. This paper presents data on bond yields for three British colonies and independent Liberia along with qualitative evidence on the mechanics of borrowing by West African governments. It suggests that a variety of imperial interventions were important in reducing borrowing costs for the poorer periphery of the empire. The contrasting case of Liberia shows that supersanctions did not fully replicate the effects of colonial rule.